PARENTS' COMMUNICATION IN MOTIVATING THEIR CHILDREN TO FOLLOW LEARNING AT HOME TAHFIDZ KHAIZERANI KAPAS III KLAMBIR V HAMPARAN PERAK - Nurhalima Tambunan; Marasakti Bangunan (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of the study is to find out the communication of parents in motivating their children to follow learning at Tahfidz Khaizerani Dusun III Klambir V Kebun, Hamparan Perak District, especially in The Dusun Kapas I, II, III, to find out How Parents Provide Motivation to Children Following Learning at Tahfidz Khaizerani Kapas III Klambir V Kebun Hamparan Perak. This research was carried out for six months to obtain data and information researchers using qualitative approaches and collecting data through secondary and primary data by conducting observations and interviews With related parties. Study at the house Tahfiz Khaizarani is a village program that seeks to implement the eradication program of Arab illiteracy, which in practice is guided by students of the final semester of University Pembangunan of Panca Budi Islamic Religious Education Study Program, which is carried out for free, the implementation of this activity is carried out by students in turn and can be used as a form of practicum. The implementation of the field of children who study at the Tahfiz home has decreased in the last few months, for that there needs to be more profound research in finding the cause of the decline in santri following education. Parents establish patterns of communication with their children. The main thing that needs to be observed first is how parents try to know and understand the characteristics of each child. That way, parents indirectly already know the key to building communication patterns between parents and their children. Keywords: Parents' Communication, Motivating, Learning at RumahTahfidz Khaizerani.